2017
DOI: 10.1007/s00228-017-2223-5
|View full text |Cite
|
Sign up to set email alerts
|

Lack of essential information in spontaneous reports of adverse drug reactions in Catalonia—a restraint to the potentiality for signal detection

Abstract: More than one third of the reports coming from manufacturers did not include information that is considered a limiting factor to evaluate any causal relationship, and can be an issue for the detection of safety signals. To take advantage of this huge amount of potentially important information that is almost useless at present, data mining tools and new algorithms should be developed and tested with the aim of finding formulas to deal with a huge amount of low quality data without losing it, nor generating a n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 13 publications
2
15
0
Order By: Relevance
“…Table shows that age information was not available in 5.9% of the reports and that the sex of the patient was not included in 3.8% of the reports. Similar results were obtained in a previous study . Because patient information such as age or sex were not required to evaluate documentation grading, such missing information would not affect the quality evaluation of ADR reports by the WHO documentation grading scheme.…”
Section: Discussionsupporting
confidence: 84%
“…Table shows that age information was not available in 5.9% of the reports and that the sex of the patient was not included in 3.8% of the reports. Similar results were obtained in a previous study . Because patient information such as age or sex were not required to evaluate documentation grading, such missing information would not affect the quality evaluation of ADR reports by the WHO documentation grading scheme.…”
Section: Discussionsupporting
confidence: 84%
“…It is also important to note that improvements in the quality of ADR reports are also a critical measure, and unfortunately this was not investigated in any of the included studies. Studies have shown that the filling quality of ADR reports in national pharmacovigilance databases are extremely poor resulting in the inability to apply algorithms to determine any possible causal relationships between the medicine and ADR . This may be due to constraints within global pharmacovigilance legislations that mandate ADR reporting for pharmaceutical companies, who would focus on reporting ADRs just to comply with these regulations, even for cases with minimal information .…”
Section: Discussionmentioning
confidence: 99%
“…This may be due to constraints within global pharmacovigilance legislations that mandate ADR reporting for pharmaceutical companies, who would focus on reporting ADRs just to comply with these regulations, even for cases with minimal information . The same studies showed that the quality of ADR reports from HCPs are much higher than those received from the pharmaceutical companies indicating that those who choose to report are more motivated or had better knowledge of pharmacovigilance . Therefore, the focus of strategies should be to address the barriers associated with the voluntary nature of HCP reporting to increase the quantity of reports that are of high quality.…”
Section: Discussionmentioning
confidence: 99%
“…Although the spontaneous reporting system is a keystone of pharmacovigilance, the incompleteness of data is a major concern for causality assessment [1, 2]. Since causal assessment of adverse events (AEs) cannot be made without demographic or clinical information, completeness in reporting is important for the early detection of adverse drug reactions.…”
Section: Introductionmentioning
confidence: 99%